2016
DOI: 10.5772/62291
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of ZnO/TiO2 Heterogeneous Nanofibres and Their Photocatalytic Behaviour and Mechanism towards Rhodamine B

Abstract: In this study, novel titanium dioxide (TiO 2) and zinc oxide (ZnO) hybrid photocatalysts in the form of nanofibres were fabricated by a facile method using electrospinning followed by a calcination process. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) were employed to investigate the morphology and structure of the heterogeneous nanofibres. The photocatalytic performances were evaluated via the photodegradation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Our results imply that the photocatalytic activity of the synthesized samples depends not only on their BET surface area or crystallinity but can rather be attributed to dispersion and surface morphology. Moreover, based on research reports regarding heterogeneous photocatalysis [ 31 , 62 , 63 ], we propose a probable mechanism (see Figure 11 ) and reactions of the photodegradation of organic dyes using TiO 2 -ZnO oxide materials. …”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Our results imply that the photocatalytic activity of the synthesized samples depends not only on their BET surface area or crystallinity but can rather be attributed to dispersion and surface morphology. Moreover, based on research reports regarding heterogeneous photocatalysis [ 31 , 62 , 63 ], we propose a probable mechanism (see Figure 11 ) and reactions of the photodegradation of organic dyes using TiO 2 -ZnO oxide materials. …”
Section: Resultsmentioning
confidence: 83%
“…The authors evaluated the photocatalytic activities of different TiO 2 -ZnO composites in the photodegradation of Rhodamine B (RhB) under irradiation with 420 nm visible light. ZnO/TiO 2 hybrid nanofibers were prepared via electrospinning by Chen et al [ 63 ]. Based on the photodegradation of RhB, it was shown that the synthesized products exhibited high degradation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible to obtain a greater photo-catalytic reaction speed and then a greater photo-catalytic activity because electron-hole separation is favored, decreasing the recombination of these charge carriers [25][26][27][28][29]. Also, they have been used for photo-anodes in dye-sensitized solar cells [30], in ink degradation [31][32][33][34], herbicide degradation [35], humidity sensors [36][37][38], and, photo-anodes for water splitting [39,40] among other applications.…”
Section: Introductionmentioning
confidence: 99%
“…Organic dyes utilized in textile, cosmetic and food industrials, as a class of causative agents of water pollution cannot be degraded using microorganisms in water, leading to disruption of food chains, the death of aquatic animals and human diseases. This is mainly attributed to coloured organic compounds suppressing photosynthetic reactions through inhibiting sunlight penetration into aquatic ecosystems [1,2]. Customary physical and biological remediation techniques have been proven not to be effective in removing organic dye molecules [3].…”
Section: Introductionmentioning
confidence: 99%